Pengembangan Manajemen Pembelajaran Online (Daring) Berbasis Website & Offline (Luring) Berbasis Model Investasi Kelompok untuk Meningkatkan Kemandirian Belajar dan Prestasi Belajar Pak pada Masa Pandemi Covid 19 (Studi Pada SMA Negeri 7 Saparua, Kabupat - Cynthia L. Sapulette; Juli Ririhena (Journal on Education, 2024)
This study aims to determine the validity, practicality, and effectiveness of the development of online (web-based) and offline (group-based) learning management based on the investment model while simultaneously enhancing students' learning independence and academic achievement in Religious Education (PAK) during the COVID-19 pandemic (Study at SMA Negeri 7 Saparua, Central Maluku Regency) through R&D research using the Four D (4D) model. Based on the research results, the following is indicated: (1) The validation results for several instruments include: Teaching Material with a score of 4.00, participant responses 4.65, teacher responses 4.73, teacher's ability to manage learning 4.80, student activity 4.73, lesson plans 4.68, achievement tests 4.80, and learning website 4.79. These instruments fall into the valid and very valid categories, meaning that the learning tools and supporting instruments meet the validity criteria. (2) Practicality test: Online learning management based on a website and offline group investigation model, through data analysis of practicality components, shows an average percentage of teacher responses at 91.01%, categorized as very positive, and an average percentage of student responses at 80.55%, categorized as positive. (3) The effectiveness of the learning tools can be seen from the average score of teachers' ability to manage learning, which is 4.72, categorized as very good, the average percentage of student activity is 76.16%, categorized as good, and the average percentage of test results is 90.86%, categorized as high, with a classical completion rate of 100% of students achieving completeness.